2015
DOI: 10.1128/iai.02345-14
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella pneumoniae Translocates across the Intestinal Epithelium via Rho GTPase- and Phosphatidylinositol 3-Kinase/Akt-Dependent Cell Invasion

Abstract: bKlebsiella pneumoniae is an important pathogen that causes hospital-acquired septicemia and is associated with the recent emergence of community-acquired pyogenic liver abscess (PLA). Clinical typing suggests that K. pneumoniae infections originate from the gastrointestinal reservoir. However, the underlying mechanism remains unknown. Here, we have sought to determine how K. pneumoniae penetrates the intestinal barrier. We identified that bacteremia and PLA clinical isolates adhered to and invaded intestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 63 publications
1
44
0
Order By: Relevance
“…12,13 Our recent study suggested that transcellular translocation is exploited by K. pneumoniae to migrate from the gut flora into other tissues, resulting in systemic infections. 14 However, the initial stages of K. pneumoniae infection remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Our recent study suggested that transcellular translocation is exploited by K. pneumoniae to migrate from the gut flora into other tissues, resulting in systemic infections. 14 However, the initial stages of K. pneumoniae infection remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…PI3K is an essential downstream factor of the integrin signalling pathway that regulates cytoskeleton organisation and is critical for many pathogens to invade host cells (Banerjee et al, ; Faulstich, Bottcher, Meyer, Fraunholz, & Rudel, ; Hsu et al, ; Lambotin et al, ; Lussier, Basora, Bouatrouss, & Beaulieu, ; Smerling, Tang, Hofmann, & Danker, ). Therefore, we further investigated if PI3K is involved in V .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a study showed that the GI K.pneumoniae could invade and penetrate the intestinal epithelium, which indicated that GI K.pneumoniae could cause extraintestinal infections. This transcellular translocation mechanism is exploited by K. pneumoniae strains from the gut ora to cause systematic infection [27]. Although there was a close relationship between colonization and infections, the homologous relationship between the GI colonized isolates and extraintestinal isolates had not been reported yet.…”
Section: Discussionmentioning
confidence: 99%